PEMUTUSAN HUBUNGAN KERJA (PHK) DALAM HUKUM KETENAGAKERJAAN INDONESIA - Junaidi Abdullah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2013)
Working relationship is the relations between employers and workers/ laborers under working contracts, which has elements of jobs, wages, and commands. However, working relations is not always fine, sometimes there is dispute between employers and workers. The disputes may cause termination of employment or layoff. The termination may be initiated by employers, workers, law and the decision of dispute resolution institution.When layoff occurs, there is compensation in the form of severance pay, gratuity and compensation. The layoff dispute can be resolved through two paths: the first way is through bipartite, mediation and consolidation; and the second is through the industrial relation court.Keywords: layoff, compensation, dispute resolution